Lemko Region in the Light of the Polish Declarations of Admiration and Friendship for the United States - Ksenicz, Igor (Sensus Historiae, 2023)
In 1926, 5,5 million of citizens of the Republic of Poland signed the Polish Declarations of Admiration and Friendship for the United States. Apart from Poles, there were also representatives of national and ethnic minorities among the signatories of the document. The initiative covered public schools en masse. The lists with signatures of pupils are an interesting, yet less explored source on social relations in interwar Poland. In the article, the author analyzes signatures collected in Lemko villages of the Gorlice district. The analysis included three aspects: (1) anthroponymy – first names and family names of Lemkos in 1920s; (2) condition of education in the Lemko Region during that period; (3) social relations before the displacements of the Ruthenian-Ukrainian population in 1940s. The picture of the Lemko Region emerging from the analysis of the Declaration… confirms the current state of knowledge. In the area they inhabited, Lemkos were the predominant ethnic group. Ruthenians were characterized by conservatism, which is confirmed by their giving the children traditional Christian names. From the late 18th century to 1920s, over 100 new family names emerged in the Lemko Region, which testifies i.a. to migrations to this territory. The vast majority of schools attended by Lemkos participated in the initiative of collecting the signatures under the Declaration… Among the names of teachers recorded on the lists, there are Lemko social activists, mainly of Ukrainian orientation.